The role of transbronchial cryobiopsy and surgical lung biopsy in the diagnostic algorithm of interstitial lung disease. (3rd March 2015) - Hagmeyer, Lars; Theegarten, Dirk; Wohlschläger, Jeremias; Treml, Marcel; Matthes, Sandhya; Priegnitz, Christina; Randerath, Winfried J.
Abstract: Background and Aims: It is not yet known if transbronchial cryobiopsy (TCB) is a reliable and safe diagnostic tool in the investigation of interstitial lung disease (ILD). To date, there have been no studies directly comparing the value of TCB with that of surgical lung biopsy (SLB). The study was initiated to determine whether the samples taken by TCB lead to a reliable diagnosis and whether SLB can be avoided in a relevant percentage of cases. Methods: We analyzed 32 subjects with suspected ILD who underwent a TCB. Subjects' baseline characteristics, pathological findings after TCB and SLB, and complication rates were analyzed. The pathological inter‐rater agreement was quantified statistically. Results: The overall inter‐rater agreement concerning TCB sample evaluation was good with a kappa value of 0.80. In 23/32 cases (72%), the findings from the TCB showed a strong congruence with all other clinical data, thereby enabling a definitive diagnosis. Eight of the remaining nine subjects gave their consent for an SLB, which led to a definitive histological diagnosis in six cases (75%). Following TCB, pneumothorax occurred in 6/32 subjects (19%) and endobronchial bleeding was moderate in 8/32 (25%) and was severe in 17/32 cases (53%). Conclusion: This is the first study to correlate histological results and complications following TCB and SLB in ILD subjects, some of whom underwent both procedures. TCB is a suitable diagnostic tool in ILD, potentially completely dispensing with the need for an SLB in some cases. In all cases, an interdisciplinary case evaluation is necessary as a final step.